Bond market modelling using a trinomial tree - Jelena Artamonova; Remigijus Leipus (Lietuvos Matematikos Rinkinys)
In this paper a generalization of the discrete-time Ho–Lee model to the trinomial case is considered. The necessary and sufficient conditions for such a bond model to be arbitrage-free and path independent are established.